Feasibility of volleyball technics video in physical education for senior high school - Mubar, Muhammad Yusran Yusuf; Arnidah, Arnidah; Hasyim, Nurhikmah; Hakim, Abdul (Universitas Negeri Yogyakarta, 2024)
This study aims to (1) identify the needs of instructional video media in subjects related to physical education. (2) Designing instructional video media on subjects related to physical education. (3) Measuring instructional video media's validity, practicality, and effectiveness on Physical Education subjects. This study uses the ADDIE Research and Development Model approach, which is carried out through 5 stages, consisting of (1) the analysis phase, (2) the design phase, (3) the development phase, (4) the implementation phase and, (5) the evaluation phase. The research subjects were one teacher and 30 students. The results of the study are: (1) Identification of the need for instructional video media in physical education subjects shows that learning video media is needed as an alternative medium that can be used to support the teaching and learning process. (2) The design of instructional video media includes several stages, including conducting curriculum analysis, preparing teaching material scripts, and designing products. (3) Analysis of the validity, practicality, and effectiveness of learning video media products. The content/material validation results and design construct validation by experts obtained very valid categories so that learning video media products can be tested to determine the level of practicality and product effectiveness. The level of practicality and effectiveness of the product meets the criteria of being very practical and very effective.